If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -623 = u + 107 Reorder the terms: -623 = 107 + u Solving -623 = 107 + u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. -623 + -1u = 107 + u + -1u Combine like terms: u + -1u = 0 -623 + -1u = 107 + 0 -623 + -1u = 107 Add '623' to each side of the equation. -623 + 623 + -1u = 107 + 623 Combine like terms: -623 + 623 = 0 0 + -1u = 107 + 623 -1u = 107 + 623 Combine like terms: 107 + 623 = 730 -1u = 730 Divide each side by '-1'. u = -730 Simplifying u = -730
| 0.04Xy=24 | | 2x-3-4lnx=0 | | 1=0.2x-0.9x-27 | | -27=6-3p | | 4x+9x-5=138 | | 3x+1x=4x+6x-6x | | c+819=-106 | | -3t+2t-10=-2 | | 10-12y+5=2(y-8) | | -733=w+-425 | | 2x^2+9=109 | | 4n-8=-40 | | 10t+5t+t-15t=12 | | 5(x)=2x-10 | | x^2-2x+y^2-6y=-6 | | Log(6x-8)=0 | | 0(x)=2x-10 | | 2x/7-3=2 | | -9r(r+1)+6(1-3r)= | | -4=40/x*20 | | -2(x)=2x-10 | | 2(4+x)=2x+3 | | 0.5r=-15 | | 3-j=-j+3 | | 6q=84 | | x+y+2z=0 | | -34r-8=36 | | 8c-6c-c=11 | | 2k-12=4k | | 5x-8x=5x-8x | | 7x+12=8x | | -7(b+9)-2(10b-5)= |